A Bioecological Perspective of Emotional/Behavioral Challenges for Gifted Students of Color: Support Needed Versus Support Received. (June 2022) - Collins, Kristina Henry; Coleman, Mary Ruth; Grantham, Tarek C.
In this article, we highlight Bronfenbrenner's bioecological approach to explore identity formation and the impact of dynamic interactions between the student and their environment in the development of self-concept, self-esteem, and self-efficacy. We examine the complex interactions between student identity and the systems of support that are meant to help students achieve academic success; looking specifically at how the intersections between race, ethnicity, learning exceptionalities, and socioeconomic standing affect students who are identified as gifted and as emotionally/behaviorally challenged. Our call to rethink the services offered to students in special and gifted education leads to a proposed culturally responsive and enhanced multi-tiered system of supports (CR-MTSS). We believe the CR-MTSS approach can better address the strength of students with or a risk for developing emotional and behavioral challenges, supporting each student's success.